Clinical aspects of the three major genetic forms of long QT syndrome (LQT1, LQT2, LQT3) - Kutyifa, Valentina (Ann Noninvasive Electrocardiol, 2018)
BACKGROUND: A comprehensive report on the clinical course of the three major genotypes of the long QT syndrome (LQTS) in a large U.S. patient cohort is lacking. METHODS: Our study consisted of 1,923 U.S. subjects from the Rochester‐based LQTS Registry with genotype‐positive LQT1 (n = 879), LQT2 (n = 807), and LQT3 (n = 237). We evaluated the risk of a first cardiac event (syncope, aborted cardiac arrest, or sudden cardiac death, whichever occurred first) from birth through age 50 years. Cox proportional hazards regression models incorporating clinical covariates were used to assess genotype‐specific risk of cardiac events. RESULTS: For all three genotypes, the cumulative probability of a first cardiac event increased most markedly during adolescence. Multivariate analysis identified proband status and QTc > 500 ms as predictors of cardiac events in all three genotypes, and males <14 years and females >14 years as predictors of cardiac events in LQT1 and LQT2 only. Beta‐blockers significantly reduced the risk of cardiac events in LQT1 (HR: 0.49, p = .002) and LQT2 patients (HR: 0.48, p = .001). A trend toward beta‐blocker benefit in reducing cardiac events was found in LQT3 females (HR: 0.32, p = .078), but not in LQT3 males (HR: 1.37, p = .611). CONCLUSION: Risk factors and outcomes in LQTS patients varied by genotype. In all three genotypes, proband status and prolonged QTc were risk factors for cardiac events. Younger males and older females experienced increased risk in LQT1 and LQT2 only. Beta‐blockers were most effective in reducing cardiac events in LQT1 and LQT2, with a potential benefit in LQT3 females.